The Effect of Harvest Age on Different Regrowth on Chicory (Cichorium intybus L.) Forage Yield by Intercropped with Pennisetum purpureum cv. Mott - Nur Zaini; Nafiatul Umami; Chusnul Hanim; Andriyani Astuti; Bambang Suwignyo (Buletin Peternakan, 2021)
This research was carried out to examine the chicory forage yields on different regrowth which were intercropped with Pennisetum purpureum cv. Mott (dwarf elephant grass) on different regrowth due to various harvest age. The research was conducted in the Laboratory of Forage and Pasture, Faculty of Animal Science UGM for 7 months, with a split-plot design and analyzed by Duncan with a total of 9 plots and an area of 2.5x2.5 m2 for each plot. The main plot was the harvest age treatment (30, 45, and 60 days) and the subplot was the regrowth (first and second). In the first stage, as many as 9 cuttings of dwarf elephant grass in one plot were planted with a spacing of 1x1 m2 until the plant height reaches 10 to 15 cm, then the chicory seeds were spread among the dwarf elephant grass plants with the sand mixture. The results showed the harvest age had a significant effect (P<0.05) on chicory's plant height, fresh forage yield, dry matter content, dry matter digestibility, and organic matter digestibility. The 30 to 45 days harvest age performed a higher fresh production more than the 45 days to 60 days harvest age. The 60 days harvest age and second regrowth yielded the highest mixed fresh production compared to the other harvest ages, namely from 12.50 ton/ha to 25.26 ton/ha. Based on the research results showed that the older the harvest age (60 days) increased the biomass of plant production but decreased the plant digestibility. The second regrowth was able to produce higher than the first regrowth, but there was no significant effect on the dry matter content and forage digestibility.